1994
DOI: 10.1128/iai.62.8.3447-3453.1994
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of neuron impairment by oral infection with verotoxin-producing Escherichia coli O157:H- in mitomycin-treated mice

Abstract: We developed a mouse model of acute encephalopathy induced by verotoxin 2 variant (VT2v)-producing Escherichia coli. Three-week-old mice were inoculated intragastrically with approximately 10(10) CFU of E. coli O157:H- strain E32511/HSC and simultaneously given an intraperitoneal injection of mitomycin (MMC; 2.5 mg/kg). Drinking water containing 5 g of streptomycin sulfate per liter was given ad libitum from 3 days before the infection. From 1 to 2 days after bacterial inoculation, clinical features including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(60 citation statements)
references
References 48 publications
5
51
0
1
Order By: Relevance
“…15 Fujii et al , however, reported that vero toxin (VT) 2 was toxic directly to both endothelial cells and neurons in mitomycin-treated mice irrespective of the deterioration of renal function. 16 In the present study we found that an average daily increase of serum LDH and creatinine levels were useful to predict neurological abnormalities in complete HUS patients. The present data might suggest that the deterioration rate of renal function was linked to the pathogenesis of neurological abnormalities in patients with complete HUS caused by E.coli O157, although an accelerated average daily increase of serum LDH indicated also a refl ection of tissue damage, including to the blood vessels of the brain.…”
Section: Discussionsupporting
confidence: 50%
“…15 Fujii et al , however, reported that vero toxin (VT) 2 was toxic directly to both endothelial cells and neurons in mitomycin-treated mice irrespective of the deterioration of renal function. 16 In the present study we found that an average daily increase of serum LDH and creatinine levels were useful to predict neurological abnormalities in complete HUS patients. The present data might suggest that the deterioration rate of renal function was linked to the pathogenesis of neurological abnormalities in patients with complete HUS caused by E.coli O157, although an accelerated average daily increase of serum LDH indicated also a refl ection of tissue damage, including to the blood vessels of the brain.…”
Section: Discussionsupporting
confidence: 50%
“…Fujii et al proved that verotoxin impairs B B B in a mouse model of acute encephalopathy induced by infection with VTEC and that myelin sheath destruction and axonal edema were caused by the direct cytotoxic effect of verotoxin. 11,12 So, the possibility exists that local breakdown of BBB caused by verotoxin produced the edema and widespread lesion like ANE in our case. Gadolinium enhancement in acute stage and elevation of myelin basic protein in CSF may support the impairment of BBB and myelin sheath destruction caused by verotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…Although the e¡ect of antimicrobial agents on EHEC in vitro has been reported [9,10,19], the therapeutic e¡ect of antimicrobial agents on EHEC infected animals has yet to be reported. Previously we have established the mouse model with EHEC E32511/HSC strain [13]. In our mouse model, a large amount of EHEC (10 9 CFU) was inoculated and the release of VT2c was increased by MMC injection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a mouse model with EHEC given orally and mitomycin C (MMC) intraperitoneally [13]. It has been reported that VT production by EHEC is increased in vitro by the addition of MMC to the culture, possibly as a result of the phage induction [14,15].…”
Section: Introductionmentioning
confidence: 99%